Problem with nonlocal condition on the free boundary - Takhirov, Zh. O.; Turaev, R. N. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We investigate the one-phase Florin problem for a parabolic equation with nonlocal condition. Theorems one the existence and uniqueness of a solution are proved, and a priori estimates for the solution are obtained.